Examining the preliminary effect of a randomized control trial of Tele‐Savvy, an online psychoeducation program, on insomnia and sleep quality: Dementia care research (research projects; nonpharmacological) / Behavioral interventions. (7th December 2020) - Brewster, Glenna S; Higgins, Melinda; Yeager, Kate; Bliwise, Donald; Hepburn, Kenneth
Abstract: Background: Sleep disturbance is prevalent among caregivers of persons living with dementia. Tele‐Savvy is an online psychoeducation program that seeks to improve caregivers' knowledge and skill about their role, and reduce their distress. Caregivers (N=220) were recruited into an NIA‐sponsored trial and randomly assigned to immediate participation in Tele‐Savvy, an attention control condition (Healthy Living), or usual care. This study aims to examine the preliminary impact of Tele‐Savvy on sleep quality (Pittsburgh Sleep Quality Index) and insomnia (Insomnia Severity Index) in the first 20 cohorts of caregivers using data gathered at baseline, 3 and 6 months. Improving sleep quality was not an expected outcome of the study, but we sought to examine whether an active mastery‐focused intervention or an attention condition focused on healthy living might affect this important domain. Methods: Multilevel mixed models were used to test for group, time, and group‐by‐time effects for sleep quality and insomnia. Results: On average, caregivers were 64 years old; 72% were White and 23% were African American. At baseline, 50% of the caregivers had poor sleep quality (PSQI > 5). In addition, African Americans had significantly worse insomnia (p=.012; African Americans: Mean (M)‐10.5, standard deviation (SD)‐7.8; Whites: M‐6.2, SD‐5.8;) and sleep quality (p=.006; African Americans: M‐8.0, SD‐4.0; Whites: M‐5.4, SD‐4.1) scores. We found no significant group‐by‐time effect on insomnia (p=.22) or sleep quality (p=.20). For sleep quality, the Tele‐Savvy group reported small decreases over time with the mean remaining above the clinical cut‐off of 5 (7.2 at baseline, 6.6 at 6 months). In contrast, the attention control and waitlist control groups experienced worsening of sleep quality (attention control: 5.9 at baseline to 6.5 at 6 months; waitlist control: 5.6 at baseline to 6.5 at 6 months). Conclusion: At this intermediate point of analysis, that neither the Tele‐Savvy intervention nor the control condition focused on health and well‐being (but not on sleep), were effective at improving caregivers' sleep quality. It is necessary to develop interventions specific to sleep disturbance or to integrate behavioral or psychoeducational components that target the sleep disturbance into psychoeducational interventions.